Nanotecnologie e alimenti tra etica e diritto prospettive della regolazione nell’Unione europea (Glocalism: Journal of Culture, Politics and Innovation, 2014)
The employment of emerging technologies within the agro-food sector implies considerations of legal, ethical, economic and social nature, which require specialists from different fields of study to confront and cooperate. This paper focuses on the main issues that have been arising in the regulation of nanotechnologies applied to the food sector: the relationship between science and law in defining new scientific entities; the problems related to the procedures of risk assessment and risk management; the role played by ethics in the framework of EU policy; the EU regulatory approach to nanofood.
Keywords: nanotechnologies; regulation; risk assessment; risk management; ethics; soft law